PERAN PEMBELAJARAN TARI TRADISIONAL DALAM PENGUATAN IDENTITAS BUDAYA SISWA DI MTS MUHAMMADIYAH SUNGAI BATANG - Resha Gustina Putri; Rahma Novita Sari; Jupriani; Indrayuda (STKIP Subang, 2026)
This study aims to describe and analyze the role of traditional dance learning in strengthening students’ cultural identity at MTs Muhammadiyah Sungai Batang. The study was motivated by the increasing influence of globalization and technological development, which have the potential to reduce young people's understanding and appreciation of local culture. In this context, traditional dance learning is considered a cultural education medium capable of instilling cultural values while reinforcing students’ cultural identity. This research employed a qualitative approach with a case study design. The participants consisted of the school principal, arts and culture teachers, students, and cultural figures selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. Data validity was ensured through source triangulation, technique triangulation, member checking, and prolonged engagement. The findings reveal that traditional dance learning plays a significant role in strengthening students’ cultural identity. It not only develops artistic skills but also serves as a medium for transmitting Minangkabau cultural values. Through the learning process, students gain a deeper understanding of the history, meanings, and cultural values embedded in traditional dances. Furthermore, traditional dance learning fosters pride in local culture, enhances cultural awareness, and strengthens students’ sense of belonging to Minangkabau cultural identity. Dance practices and performances also contribute to character building through the development of discipline, cooperation, responsibility, and respect for local cultural heritage. In conclusion, traditional dance learning at MTs Muhammadiyah Sungai Batang functions as an effective cultural education medium for strengthening students’ cultural identity. Therefore, it should continue to be developed as part of efforts to preserve local culture and build the character of younger generations in the era of globalization.